The Effect of Motivation, Work Environment and Job Training on Increasing Employee Performance at PT PG Candi Baru Sidoarjo - Murdaningsih, Sri Rahayu; Hermawan, Sigit; Supardi, Supardi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
This study seeks to evaluate how motivation, work environment, and job training affect employee performance. The study involved a sample of 106 employees, selected through a simple random sampling technique to ensure representative results. The analysis was conducted using Structural Equation Modeling with Partial Least Squares (SEM-PLS), a method that is well-suited to handle complex models and provides insight into the relationships between variables. The results revealed that motivation has a significant positive impact on employee performance. Highly motivated employees tend to perform better in their roles. In addition, the work environment plays a significant role in enhancing employee performance; a supportive and conducive work environment contributes to higher productivity and job satisfaction. Furthermore, job training has also been shown to have a positive impact on employee performance. Well-designed training programs that are relevant to the employee’s role help improve their skills and knowledge, which in turn improves employee performance.